Musical Gesture and Transcendence in Bloch’s Nigun (Per Musi, 2021)
In 1923, Ernest Bloch composed “Baal Shem: Three Pictures of Chassidic Life”. This musical work has three parts representing the Hasidic overground, respectively “Vidui”, “Nigun” and “Simchas Torah”. The second movement became a widely known piece and incorporated into the repertoire of violinists. Bloch associates the nigun, interpreted by the human voice, with the violin, putting the instrument in the place of the Cantor or Rabbi. The violin incorporates the praying figure that characterizes the nigun, including gestures, and using music as a vehicle from materiality to transcendence (devekut). Through expressive analysis, this essay aims to show the similarities between Nigun's composition and the homonymous musical genre, emphasizing musical gesture and interpretative cadential movement, and to awaken some thoughts about the theme, without the intention of presenting conclusive answers.